2014
DOI: 10.1016/j.jhydrol.2014.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Documentary evidence of past floods in Europe and their utility in flood frequency estimation

Abstract: This review outlines the use of documentary evidence of historical flood events in contemporary flood frequency estimation in European countries.The study shows that despite widespread consensus in the scientific literature on the utility of documentary evidence, the actual migration from academic to practical application has been limited. A detailed review of flood frequency estimation guidelines from different countries showed that the value of historical data is generally recognised, but practical methods f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(105 citation statements)
references
References 72 publications
(63 reference statements)
0
105
0
Order By: Relevance
“…Overall, the widespread recommendation of using ML based methods when historical information is available at a location of interest documented in [8] seems to be a sensible one. Within the FEH Local project the sensitivity of the estimation procedures to model misspecifications was also investigated, showing that the reduction in uncertainty is still present even when the historical information might be slightly imprecise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the widespread recommendation of using ML based methods when historical information is available at a location of interest documented in [8] seems to be a sensible one. Within the FEH Local project the sensitivity of the estimation procedures to model misspecifications was also investigated, showing that the reduction in uncertainty is still present even when the historical information might be slightly imprecise.…”
Section: Discussionmentioning
confidence: 99%
“…PWMs and L-moments are widely used in hydrology, due to their good performance with small samples and the simplicity of their calculation. Nevertheless the use of PPWMs for the estimation of the distribution parameters in the presence of historical information seem to be rare [8]. Since the methods used in the UK for flood frequency analysis are based on the L-moments framework, the use of PPWM when historical data are available might open the way to the routine inclusion of historical events in flood risk assessment.…”
Section: Partial Probability Weighted Momentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example rainfall-runoff models use information on the catchment to provide estimates of the entire hydrograph, for rainfall events of given rarity. ReFEH (Kjeldsen 2007) is the model used in the UK within the Flood Estimation Handbook, but several other models are proposed in the literature. In general, when estimating flood frequency curves, it would be ideal to use as much knowledge as possible about the site for which the estimation is carried out, combining both the hydrological knowledge of the analysis and using all available data in the best possible way.…”
Section: Statistical Models For the Frequency Of Extremes Eventsmentioning
confidence: 99%
“…A recent review by Kjeldsen et al (2014) observed a scarce use of historical data for frequency estimates in 16 countries of Europe, identifying three main reasons: (1) the lack of unified database depositories, (2) uncertainty associated with discharge estimates, (3) concerns about violation of stationary assumption when using historical data, i.e. annual probabilities are equated to historical frequencies of occurrence.…”
Section: Flood Frequency Analysismentioning
confidence: 99%